Beyond competencies: Consensus on entrustable professional activities and milestones for dietetics education - Begley, Andrea (Wiley-Blackwell, 2019)
Entrustable professional Activities (EPAs) describe independently executable, observable, measurable practice tasks mapped to competencies. Students achieve entrustment status by passing a set of milestones or behavioural descriptors that mark the developing levels of performance for given EPAs. The aim of this study was to develop consensus on innovative EPAs and milestones in dietetics education to provide students, practice educators and academics with shared mental models to assess entry-level competence. Outcomes from four national workshops with academic dietitians and experienced supervisors (n = 100) resulted in four draft EPAs and descriptive milestones for novice, beginner, competent and expert levels of performance. A consensus survey was designed to measure agreement with EPAs and milestones and was sent to workshop participants (n = 98). The survey response rate (37%) included 18 academics, seven university supervisors and 11 practice educators. Agreement on the EPAs ranged from 73% to 100%. Comments related specifically to consideration of higher order performance of tasks. The novice (starting placement) milestones were the least agreed (lowest 83%) with comments indicating descriptors were not expecting enough of the student starting placement or were undervaluing the ability of students and their prior learning. These comments were used to refine EPAs and milestone descriptors. This work has supported the development of shared mental models of competence amongst academics and supervisors across Australia. EPAs and milestones will ultimately lead to improved quality of assessment and students and graduates who are able to take greater responsibility for, and with a richer understanding of, their learning. Funding source: Curtin QUT teaching grant.